Gambaran Penggunaan Obat Anestesi di Instalasi Bedah RSI PKU Muhammadiyah Pekajangan - Musa Fitri Fatkhiya; Nitya Rofiana Arrizka (Journal Borneo, 2023)
Induction of anesthesia, each patient can get a variety of premedications. The selection of anesthetic drugs should be based on patient characteristics and conditions associated with surgery and costs. This study aims to describe the use of anesthetic drugs in the Surgical Installation of RSI PKU Muhammadiyah Pekajangan in the period May-July 2022. The method used in this research is descriptive observational. The results of the study showed the use of fentanyl 100 mcg/2mL 130 (27.43%), recofol-N 10 mg/mL 101 (21.31%), KTM 100 mg/mL 89 (18.78%), sevodex 250 mL 50 (10.55%), sedacum 5 mg/5mL 39 (8.23%), tramus 25 mg 38 (8.02%), tramus 50 mg 14 (2.95%), and Isorane/Isoflurane 250 mL 13 (2.74) %). So it can be concluded that the most widely used general anesthetic drug was fentanyl 100 mcg/2mL of 27.43%.